Aplikasi Mobile Untuk Sistem Presensi Dosen dan Karyawan Universitas Kristen Petra - Melinda Christy Roedyanto; Justinus Andjarwirawan; Agustinus Noertjahyana (Jurnal Infra, 2019)
In carrying out daily activities, employees need to do attendance, which is one of the requirements for the salary calculation process. Presence is the level of attendance of employees regarding responsibility. Every permanent lecturer and permanent employee of Petra Christian University always makes a presence when entering and when returning. In attendance attendance records, there are many found in attendance data that is empty (not recorded) or twin during the recapitulation process at the end of the period. This happens because there are employees who forget, feel they have attended, or are not sure whether the presence data has been recorded or not. So that employees make a presence again to ensure that their attendance data is recorded.At this time, to check the attendance data, the employee must enter protal sim.petra.ac.id first. Then every time you enter, the employee needs to fill in the username and password for the login process. This is a matter that is considered less practical and efficient. Because only to check attendance attendance every day, employees need to enter the portal and login first.With the creation of mobile applications, it can make the checking process more practical and efficient. Employees only need to log in at the beginning when they first download the application. In the application there is also a graph of attendance calculations within an interval of one week. The graph is intended so that employees know whether in one week the employee is exposed to the presence limit or not. In addition, it can also be used to remind employees if on the previous day, attendance data was empty, the time of arrival and the time of return. If this happens, the employee can also submit a manual presence submission to the application.